1988
DOI: 10.1007/bf01871396
|View full text |Cite
|
Sign up to set email alerts
|

Effects of arachidonic acid and the other long-chain fatty acids on the membrane currents in the squid giant axon

Abstract: The effects of arachidonic acid and some other long-chain fatty acids on the ionic currents of the voltage-clamped squid giant axon were investigated using intracellular application of the test substances. The effects of these acids, which are usually insoluble in solution, were examined by using alpha-cyclodextrin as a solvent, alpha-cyclodextrin itself had no effect on the excitable membrane. Arachidonic acid mainly suppresses the Na current but has little effect on the K current. These effects are completel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
2

Year Published

1991
1991
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 18 publications
(13 reference statements)
0
9
2
Order By: Relevance
“…The results from the present study are inconsistent with a mechanism involving effects on the bilayer and they tend to support the idea that amphiphiles directly regulate K + channel activity for the following reasons. The notion that "detergent effects" or alterations in "membrane fluidity" (Spector, 1986;Takenaka et al, 1987Takenaka et al, , 1988Bregestovski et al, 1989) underlie the actions of fatty acids and polar lipids is open to question (Carruthers and Melchior, 1988;Cistola, Hamilton, Jackson and Small, 1988). The results from the present study not only fail to support such a mechanism but provide several lines of evidence to the contrary.…”
Section: Mechanisms Of Amphiphile Actioncontrasting
confidence: 71%
“…The results from the present study are inconsistent with a mechanism involving effects on the bilayer and they tend to support the idea that amphiphiles directly regulate K + channel activity for the following reasons. The notion that "detergent effects" or alterations in "membrane fluidity" (Spector, 1986;Takenaka et al, 1987Takenaka et al, , 1988Bregestovski et al, 1989) underlie the actions of fatty acids and polar lipids is open to question (Carruthers and Melchior, 1988;Cistola, Hamilton, Jackson and Small, 1988). The results from the present study not only fail to support such a mechanism but provide several lines of evidence to the contrary.…”
Section: Mechanisms Of Amphiphile Actioncontrasting
confidence: 71%
“…A dash denote that the parameter has not been investigated, there is no effect, or that it is not applicable. a, (Takenaka et al, 1987, 1988; Premkumar et al, 1990; Rouzaire-Dubois et al, 1991; Damron et al, 1993; Villarroel, 1993; Chesnoy-Marchais and Fritsch, 1994; Honoré et al, 1994; Lee et al, 1994; Lynch and Voss, 1994; Gubitosi-Klug et al, 1995; Poling et al, 1995; Nagano et al, 1995a; Poling et al, 1996; Soliven and Wang, 1995; Wang and Lu, 1995; Nagano et al, 1997; Garratt et al, 1996; Smirnov and Aaronson, 1996; Villarroel and Schwarz, 1996; Gilbertson et al, 1997; Horimoto et al, 1997; Keros and McBain, 1997; Bogdanov et al, 1998; Bringmann et al, 1998; Devor and Frizzell, 1998; Dryer et al, 1998; Hatton and Peers, 1998; Visentin and Levi, 1998; Bittner and Müller, 1999; Colbert and Pan, 1999; Singleton et al, 1999; Yu et al, 1999; Casavant et al, 2000; Wilson et al, 2000; Holmqvist et al, 2001; Kehl, 2001; McKay and Jennings, 2001; Takahira et al, 2001; Erichsen et al, 2002; Müller and Bittner, 2002; Ramakers and Storm, 2002; Seebungkert and Lynch, 2002; Xiao et al, 2002; Danthi et al, 2003; Ferroni et al, 2003; Judé et al, 2003; Fioretti et al, 2004; Oliver et al, 2004; Sokolowski et al, 2004; Angelova and Müller, 2006, 2009; Feng et al, 2006; Kang et al, 2006; Jacobson et al, 2007; Szekely et al, 2007; Zhao et al, 2007; Börjesson et al, 2008, 2010; Guizy et al, 2008; Xu et al, 2008; Zhang M. et al, 2008; Boland et al, 2009; Koshida et al, 2009; Li et al, 2009; Wang et al, 2009; Decher et al, 2010; Börjesson and Elinder, …”
Section: Effects Of Pufa On Voltage-gated Ion Channelsmentioning
confidence: 99%
“…Finally, in 1988, by using α-cyclodextrin to dissolve the fatty acids, this group reported that long-chain PUFAs produced effects similar to medium-chain fatty acids (Takenaka et al, 1988). Intracellularly applied AA (20:4) reversibly suppressed the Na current of the squid giant axon with little effect on the K current.…”
Section: Effects Of Pufa On Voltage-gated Ion Channelsmentioning
confidence: 99%
“…Indirect, but potentially physiologically relevant, modulation of ion channels through an alteration of membrane composition has been proposed. This membrane destabilization is a possible mechanism of fatty acids in modifying the activity of squid giant axon Na ÷ (Takenaka, Horie, Hori, and Kawakami, 1988) and aortic smooth muscle K ÷ channels (Bregestovski, Bolotina, and Serebryakov, 1989). An important caveat is the possibility of a detergent effect of lipophilic compounds at concentrations close to the critical miceUar concentration, where aggregates of monomers disrupt membranes and can apparently create lipidic pores (Sawyer and Anderson, 1989).…”
Section: Introductionmentioning
confidence: 99%